A review of 80 assessment tools measuring water security. (24th February 2021) - Octavianti, Thanti; Staddon, Chad
Abstract: Scholars and practitioners have been working on methodologies to measure water security at a variety of scale and focus. In this paper, we critically examine the landscape of water security metrics, discussing the progress and gaps of this rich scholarship. We reviewed a total of 107 publications consisting of 17 conceptual papers and 90 methodological papers that propose 80 metrics to measure water security and observed that there are two dominant research clusters in this field: experiential scale‐based metrics and resource‐based metrics. The former mainly focus on measuring the water experiences of households and its impact on human well‐being, while the majority of the latter assess freshwater availability or water resources security. We compare their approaches and the arguments used to develop them. We posit that the more local the scale and the more specific the water domain, the more meaningful results that the metrics can provide. Acknowledging the interrelationship between different water domains (e.g., water resources and water hazards) is important, but their aggregation for measurement may be problematic. We offer our views on future work in this field relating to topics beyond water, the need to conduct validation tests, and collaboration among academics and with other stakeholders. This article is categorized under: Human Water > Human Water Abstract : The landscape of water security metrics is dominated by two large research clusters: experiential scale‐based metrics (blue) and resource‐based metrics (red and green). They were identified by qualitative review and bibliometric analysis, such as through a network map of co‐occurrences of keywords.